Impact of information about health and academic benefits on parent perception of the feasibility of active transportation to school. (September 2018) - Lucken, Emma; Soria, Jason; Niktas, Mary-Ann; Wang, Tonia; Stewart, Matt; Nikoui, Ramin
Abstract: The percentage of students walking or biking to school in the United States has fallen drastically over the past decades. This decline has important implications for children's health, as walking and biking to school result in health benefits, including more physical activity and lower risk of obesity. Influencing parents to consider active transportation to school (ATS) is a necessary step in behavior change. Our research examines the impact of providing parents with information about the health and academic benefits of ATS on parent perception of ATS feasibility. Parents given information about ATS benefits were hypothesized to perceive ATS as more feasible, as measured by responding that there is an additional morning or afternoon during the week when their child could walk or bike to or from school. Treatment and control surveys were distributed to parents with children attending elementary school in Alameda County and Richmond, California. Discrete choice models developed from this data indicated that information about ATS benefits did not have a significant effect on parent perception of ATS feasibility. The two models provided further insight into ATS behavior and parent perception of ATS feasibility. Greater walk time to school, higher parent education levels, lack of sidewalks along the route to school, and child participation in after-school activities located outside the school campus decreased perception of ATS feasibility. Walk time to school, vehicle ownership, and lack of sidewalks decreased ATS behavior, while having an adult in the home with flexible work hours increased it. Minorities were less likely to participate in ATS every day. Based on these results, providing more after-school activities on school grounds, constructing sidewalks along routes to school, and locating schools in dense, mixed-use areas are supported as strategies to increase ATS behavior. Highlights: Discrete choice models used to analyze interventions' impacts on ATS behavior. Information about ATS benefits did not affect parent perception of ATS feasibility. After-school activities off the school campus decreased perception of ATS feasibility. Providing more after-school activities on school grounds could increase ATS.